Rhizoma Drynariae-derived nanovesicles reverse osteoporosis by potentiating osteogenic differentiation of human bone marrow mesenchymal stem cells via targeting ERα signaling - Qing Zhao; Junjie Feng; Fubin Liu; Qianxin Liang; Manlin Xie; Jiaming Dong; Yanfang Zou; Jiali Ye; Guilong Liu; Yue Cao; Zhaodi Guo; Hongzhi Qiao; et al. (Elsevier, 2024)
Although various anti-osteoporosis drugs are available, the limitations of these therapies, including drug resistance and collateral responses, require the development of novel anti-osteoporosis agents. Rhizoma Drynariae displays a promising anti-osteoporosis effect, while the effective component and mechanism remain unclear. Here, we revealed the therapeutic potential of Rhizoma Drynariae-derived nanovesicles (RDNVs) for postmenopausal osteoporosis and demonstrated that RDNVs potentiated osteogenic differentiation of human bone marrow mesenchymal stem cells (hBMSCs) by targeting estrogen receptor-alpha (ERα). RDNVs, a natural product isolated from fresh Rhizoma Drynariae root juice by differential ultracentrifugation, exhibited potent bone tissue-targeting activity and anti-osteoporosis efficacy in an ovariectomized mouse model. RDNVs, effectively internalized by hBMSCs, enhanced proliferation and ERα expression levels of hBMSC, and promoted osteogenic differentiation and bone formation. Mechanistically, via the ERα signaling pathway, RDNVs facilitated mRNA and protein expression of bone morphogenetic protein 2 and runt-related transcription factor 2 in hBMSCs, which are involved in regulating osteogenic differentiation. Further analysis revealed that naringin, existing in RDNVs, was the active component targeting ERα in the osteogenic effect. Taken together, our study identified that naringin in RDNVs displays exciting bone tissue-targeting activity to reverse osteoporosis by promoting hBMSCs proliferation and osteogenic differentiation through estrogen-like effects.